DIVERSITY AND DISTRIBUTION OF CODH GENES WITHIN PHYLOGENETICALLY HIGHER TERMITE GUT MICROBIAL COMMUNITIES - Fechter, Buckley D. (My University, 2013)
Termites embody a highly efficient bioreactor for converting cellulose and hemicellulose into acetate, a chemical that fuels insect energy metabolism. A highly complex nutritional mutualism between termites and their gut microbes underlies this process and gives termites the ability to subsist solely on lignocellulosic plant material. Lithoautotrophic gut bacteria known as acetogens assist with the efficiency of the reactor by utilizing the byproducts of fermentative processes, hydrogen and carbon dioxide, to form additional acetate. This retains carbon and energy in the system making it available to the host. As termites have evolved, their gut tracts have become more compartmentalized. It remains unknown whether this compartmentalization has distributed certain acetogenic bacteria within different gut compartments. A gene of particular importance in understanding the diversity and distribution of acetogenic metabolism is cooS, which encodes carbon monoxide dehydrogenase (CODH), an enzyme that unites the methyl branch with the carbonyl branch of the acetogenic pathway. Degenerate CODH gene PCR primers along with cloning, restriction length polymorphism analysis and sequencing were employed to investigate CODH genes in five phylogenetically higher termites and individual gut segments of one of these termites, Gnathamitermes perplexus. The aim of this research was to reveal the diversity of CODH genes in several higher termites and to determine whether phylogenetic or functional differences exist among the different gut segments in one such termite. These analyses identified three main phylogenetic groupings of CODH amino acid sequences and found that individual gut segments of G. perplexus contained different types of CODH enzymes. The results indicate that there are similarities among CODH enzymes found in a variety of higher termites but that individual gut compartments can contain different types of CODH enzymes. This suggests that axial stratification of acetogenic metabolism has occurred along the length of the gut in higher termites.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science-Biology Microbiology
Keywords: Biomass conversion; Cellulose; Termites